1999
DOI: 10.1007/s004399900158
|View full text |Cite
|
Sign up to set email alerts
|

Germline origins in the human F9 gene: frequent G:C→A:T mosaicism and increased mutations with advanced maternal age

Abstract: The factor IX gene (F9) is an advantageous system for analyzing recent spontaneous germline mutation in humans. Herein, the male:female ratio of mutation ("r") in F9 have been estimated by Bayesian analysis from 59 germline origin families. The overall "r" in F9 was estimated at 3.75. The "r"s varied with the type of mutation. The "r"s ranged from 6.65 and 6.10 for transitions at CpG and A:T to G:C transitions at non-CpG dinucleotides, respectively, to 0.57 and 0.42 for microdeletions/microinsertions and large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 51 publications
3
32
2
1
Order By: Relevance
“…A paternal age effect has been demonstrated for certain conditions, most obviously for de novo achondroplasia, due to mutations at a CpG nucleotide pair [37]. Increasing paternal age, however, is not associated with an increase in de novo mutations for haemophilia A [33] or haemophilia B [38] in the limited series studied to date. In contrast, older females have a slightly higher likelihood of bearing a de novo germline mutation for haemophilia compared to younger females [38,39].…”
Section: Post-embryonic Germline Cellmentioning
confidence: 85%
“…A paternal age effect has been demonstrated for certain conditions, most obviously for de novo achondroplasia, due to mutations at a CpG nucleotide pair [37]. Increasing paternal age, however, is not associated with an increase in de novo mutations for haemophilia A [33] or haemophilia B [38] in the limited series studied to date. In contrast, older females have a slightly higher likelihood of bearing a de novo germline mutation for haemophilia compared to younger females [38,39].…”
Section: Post-embryonic Germline Cellmentioning
confidence: 85%
“…Lifelong spermatogonial stem cell divisions unique to the male germline are hypothesized to contribute to significant elevations in mutation frequency in males with age. Contrary to this hypothesis, germline mutations in the factor IX gene in hemophilia patients do not show a paternal age effect [Ketterling et al, 1993[Ketterling et al, , 1999. About three-fourths of the factor IX mutations causing hemophilia B are single-base substitutions, so the lack of evidence for a paternal age effect in factor IX is counter to the prevailing view that the risk of transmitting point mutations increases with the age of the father [Vogel and Motulsky, 1997;Crow, 2000].…”
Section: Most Data Are Consistent With Constancy Of Spontaneous Mutatmentioning
confidence: 85%
“…A mosaic PSEN1 mutation, present in approximately 8% of a proband's lymphocytes, as estimated by allele specific oligo hybridization (ASOH), was not detected by ABI sequencing; the same mutation present in about 14% of the cells of the cerebral cortex by ASOH was just barely discernible by ABI sequence analysis. It has been reported that overexposed autoradiographs of manual sequencing can detect mosaicism at levels of about 5% [Ketterling et al, 1999].…”
Section: Discussionmentioning
confidence: 99%